2021
DOI: 10.1002/elps.202100288
|View full text |Cite
|
Sign up to set email alerts
|

A conjoint multi metal‐ion iminodiacetic acid monolith microfluidic chip for structural‐based protein pre‐fractionation

Abstract: PDMS‐based multichannel microfluidic chip was designed and fabricated in a simple approach using readily available tools. UV‐initiated in situ polymerization of poly(2‐hydroxy ethyl methacrylate‐co‐di(ethylene glycol) diacrylate‐co‐N,Nʹ‐diallyl l‐tartardiamide) in an Eppendorf tube was achieved within 40 min. This polymerization process was successfully translated to a microfluidic chip format without any further modifications. Iminodiacetic acid was successfully immobilized on aldehyde functional monoliths vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…One study reported the use of monolith as a support for IMAC metal cations [105]. A poly(2‐hydroxy ethyl methacrylate‐co‐di(ethylene glycol) diacrylate‐co‐ N,Nʹ ‐diallyl l‐tartardiamide monolith prepared inside a PDMS microchip had the aldehyde functional groups modified with iminodiacetic acid to chelate Co (II), Zn (II), Ni (II), and Cu (II) and perform IMAC enrichment.…”
Section: Affinity Chromatographymentioning
confidence: 99%
See 3 more Smart Citations
“…One study reported the use of monolith as a support for IMAC metal cations [105]. A poly(2‐hydroxy ethyl methacrylate‐co‐di(ethylene glycol) diacrylate‐co‐ N,Nʹ ‐diallyl l‐tartardiamide monolith prepared inside a PDMS microchip had the aldehyde functional groups modified with iminodiacetic acid to chelate Co (II), Zn (II), Ni (II), and Cu (II) and perform IMAC enrichment.…”
Section: Affinity Chromatographymentioning
confidence: 99%
“…The monolith‐integrated microfluidic chip could pre‐fractionate four human plasma proteins (fibrinogen, immunoglobulin, transferrin, and human serum albumin) based on their surface‐exposed histidine. LC‐MS/MS detection on the second dimension wasn´t performed, but a determination by Bradford assay showed a protein recovery of approximately 95%, and the reutilization of the device was demonstrated after 3 adsorption‐desorption cycles [105].…”
Section: Affinity Chromatographymentioning
confidence: 99%
See 2 more Smart Citations